The Effectiveness of Planning in Achieving Physical Education and Sports Class Objectives from the Perspective of Secondary School Physical Education Teachers - A Field Study of Teachers in M'sila Province - - ghanem, Mouhamed el amine; harizi, abedelhadi (sports creativity, 2024)
The primary aim of this study is to determine the effectiveness of planning in achieving the objectives of teaching physical education and sports from the perspective of secondary school physical education teachers. This field study focused on a sample of teachers in the western district of M'sila Province. The researcher used a descriptive method, which is appropriate for this type of study, and employed a questionnaire to collect data and information. The sample included 20 specialized physical education and sports teachers. The key findings are: • Planning plays a crucial role in organizing time and pedagogical resources, which enhances the success of physical education and sports classes. • Planning is effective in improving communication between students and teachers, thus boosting students' academic performance